Financial Disclosure Timeliness and Market Reaction to Accounting Information (gjstudies, 2014)
This research introduces a novel methodological framework for examining therelationship between the timeliness of financial disclosures and the subsequent market reaction to accounting information, moving beyond traditional event-studyparadigms. We propose a temporal granularity model that decomposes disclosure timeliness into three distinct, non-linear dimensions: procedural latency (theinternal delay from fiscal period-end to disclosure authorization), transmission immediacy (the speed of information dissemination across market channels), and cognitive absorption lag (the time required for market participants to process and integrate the information). By applying this tripartite model to a unique longitudinaldataset of corporate disclosures from 1998 to 2004, we challenge the conventionalassumption that earlier disclosure is uniformly beneficial. Our findings reveal acomplex, context-dependent relationship. While reduced procedural latency is associated with lower immediate volatility, we identify an optimal zone for transmission immediacy; disclosures that are excessively rapid, before supporting analyticalframeworks are widely available, can lead to misinterpretation and subsequent corrective volatility. Most originally, we find that a moderate cognitive absorption lag,contrary to prevailing efficiency theory, can enhance long-term price accuracy byallowing for more deliberate analyst scrutiny and peer benchmarking. The studyfurther employs a bio-inspired optimization algorithm, modeled on fungal networkcommunication patterns, to simulate information flow and identify disclosure schedules that maximize market stability. Our results suggest that regulatory emphasison sheer speed may be suboptimal, and we propose a new metric, the IntegratedTimeliness Efficiency Score, which balances speed with market preparedness. Thisresearch contributes a fundamentally new perspective to disclosure theory, integrating concepts from information theory, behavioral finance, and complex systemsto reframe timeliness not as a simple scalar but as a multi-dimensional propertyinteracting dynamically with market ecology